Infrared thermography in the evaluation of aerospace composite materials : infrared thermography to composites - Meola, Carosena; Boccardi, Simone; Carlomagno, G. M. (Woodhead Publishing in materials., 2016)
To Chapter 3 and Introduction to Chapter 4Chapter 4. Nondestructive Testing With Infrared Thermography; 4.1. Historical Groundings; 4.2. Some Basic Concepts; 4.3. Thermographic Nondestructive Testing Techniques; 4.4. Examples of Materials Inspection With Lock-in Thermography; 4.5. Other Thermographic Methods; 4.6. Some Approaches to Application in Field; Conclusions to Chapter 4 and Introduction to Chapter 5; Chapter 5. Monitoring Load Events; 5.1. Introduction; 5.2. Some Hints on Materials Thermal Effects; 5.3. Cyclic Bending Tests; 5.4. Impact Tests; 5.5. Quasistatic Bending Tests.